2021
DOI: 10.1111/evj.13477
|View full text |Cite
|
Sign up to set email alerts
|

Equine parvovirus hepatitis

Abstract: Equine parvovirus hepatitis (EqPV-H) was first described in 2018 in a fatal case of Theiler's disease which followed the administration of an equine-origin biological product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 36 publications
(294 reference statements)
1
32
1
3
Order By: Relevance
“…Theiler's disease (TD), also known as equine serum hepatitis, is an important causative agent in fulminant hepatitis in horses [1]. TD transmission is usually associated with the inoculation of contaminated equine biological products such as tetanus antitoxin, and experimental oral transmission with viremic serum was recently demonstrated [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Theiler's disease (TD), also known as equine serum hepatitis, is an important causative agent in fulminant hepatitis in horses [1]. TD transmission is usually associated with the inoculation of contaminated equine biological products such as tetanus antitoxin, and experimental oral transmission with viremic serum was recently demonstrated [2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2011, the following four viruses have been identified as candidate etiologic agents of TD using the advanced unbiased deep sequencing technique: equine hepacivirus (EqHV), equine pegivirus (EPgV), TD-associated virus (TDAV), and equine parvovirushepatitis (EqPV-H) [8][9][10][11]. However, after the discovery of EqPV-H in 2018, EqPV-H was detected in most clinical cases of TD [2]. Additionally, several consecutive studies conducted in the USA showed that 27 out of 28 (96.4%) of the clinical TD cases were positive for EqPV-H and the results experimentally demonstrated hepatotropism and the clinical correlation of EqPV-H with TD [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations